Total Quality Management in Improving Students’ Learning Discipline at SMA Negeri 06 Bombana - Ashar, Muh.; Zakariah, M. Askari; Asra, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the implementation of Total Quality Management (TQM) in improving student learning discipline at SMA Negeri 06 Bombana through the application of National Education Standards (SNP), which include process standards, management standards, and educator and education personnel standards. The research employs a qualitative case study approach, with data collected through non-participant observation, in-depth interviews, and documentation. Data validity is ensured through triangulation, while analysis is conducted using Fishbone Analysis, identifying the causes and solutions to student discipline issues. The findings indicate that the implementation of Process Standards through planning, execution, and evaluation of learning contributes positively to enhancing student discipline. Management Standards are applied through student council (OSIS) empowerment, strict teacher supervision, and periodic evaluations to ensure the effectiveness of discipline programs. Meanwhile, Educator and Education Personnel Standards focus on improving teacher competencies in instilling discipline values and serving as role models for students. The application of TQM in school management has proven effective in fostering a sustainable discipline culture among both students and educators. With an approach involving all stakeholders, the school has successfully created an academic environment that is conducive and oriented toward character development.